Shifting Religious Authority in the AI Era:: A Comparative Study of Gen Z Trust in AI Guidance and Traditional Ulama - Untung Famuji; Ahmed Abdul Malik; Siti Nuri Nurhaidah; Sofia Fahrany (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
The rapid proliferation of Artificial Intelligence (AI) has fundamentally disrupted the landscape of Islamic communication, introducing chatbots as novel sources of religious information that challenge the traditional authority of Ulama. This study aims to analyze the shift in religious authority among Generation Z by examining the reliability of AI-generated fatwas versus traditional Islamic scholarship. Employing a qualitative virtual ethnography method, data were collected through digital observation of AI interactions and critical analysis of a sermon by Habib Abdurrahman Assegaf regarding AI errors in religious interpretation. The results demonstrate significant “algorithmic hallucination” in religious texts. Specifically, AI failed to interpret the theological context of Sahih Bukhari regarding “Al-Madinatu Tanfi Al-Khabats,” providing a literal, erroneous translation that strips away spiritual meaning. While Gen Z utilizes AI for privacy and speed, this finding proves that AI lacks scientific lineage (sanad) and spiritual taste (dzauq). The implications of this study highlight the urgency of digital literacy to prevent the trivialization of sacred texts. In conclusion, while AI functions as an efficient data aggregator, it cannot replace the authoritative role of Ulama, as authentic religious understanding requires human mentorship through talaqqi to ensure validity and contextual accuracy.